Ovarian hyperstimulation syndrome: a propos of a case - Pacheco Romero, José (2015)
Report of a case of a patient previously submitted to medical treatment surgical for primary infertility and developed as a result of the application of techniques of in vitro fertilization and embryo transfer severe symptoms of ovarian hyperstimulation syndrome (OHSS) is making a wide review of the SHO, proper handling and how to prevent it. Commenting on the management received by this patient, emphasis on management alternatives that possibly prevented the patient had reached the brink of death.